Analysis of Working Period and Working Time to Health Complaints of Fish Smoking Workers Bandarharjo, Kota Semarang, 2019 (Indian Journal of Public Health Research & Development, 2020)
Burning is very dominant process to accruing material pollutants. The smoke produced from burning coconutshells of fish smoking industry is a problem that can cause health complaints of fish smoking workers, itcan produce pollutants such as CO2, HC, NO2, and particulates. It is necessary to analyze the workingperiod and time of workers’s health complaints. The purpose of this study is to analyze the working periodand time of health complaints of fish smoking workers. The design is cross sectional, data collected byinterviews using quisionare, analysis until bivariate stage. The results, form 65 total sample, mostly workers(60 people,92.3%) working > 5 years, mostly workers (61 people, 93.8%) working > 8 hours/day, mostlyworkers have a health complaints (47 people, 72.3%), there is no significant relationship between workingperiod and health complaints (pv 0.611), there is no significant relationship between working time and healthcomplaints (pv 0.061).
Keywords: Working period, working time, health complaints.